Assessment of Genetic Diversity Among Cowpea [Vigna unguiculata (L.) Walp] Genotypes using SSR Markers - Vinay, K.; Rao, P. Jagan Mohan; Kishore, N. Sandhya; Hari, Y. (International Journal of Bio-resource and Stress Management, 2022)
In the present study, 32 genotypes of cowpea were evaluated for genetic diversity through simple sequence repeats (SSR) markers at Biotechnology laboratory, Regional Agriculture Research station, Warangal, Telangana state, India during during rabi (October−February, 2020−21). 25 pairs of SSR primers were employed to analyze the genetic diversity among the genotypes. The polymorphic bands were scored visually as present (1) or absent (0) on a binary matrix and this information was utilized in the calculation of Jackard’s similarity matrix using NTSYS-pc version 2.1. Dendrogram was constructed using the Unweighted pair Group Method with an Arithmetic mean (UPGMA) algorithm. Out of 25 markers, only eight markers have shown scorable polymorphism, while fifteen markers exhibited monomorphic banding pattern and remaining two markers showed no banding pattern. A dendrogram of these genotypes based on SSR polymorphism divided into three major clusters at 23% similarity. Genetic similarity among the genotypes ranged from 13−100% with an average of 57%. High genetic similarity of 100% was recorded between the genotypes namely WCP-4 and WCP-6, GC-1712 and PCP-1124, PGCP-69 and CPD-313. The genotypes TPTC-29 and KBC-9 appeared more divergent than remaining genotypes with 26% similarity which indicates that they are genetically more distant from other genotypes and can be utilized in crossing programmes. The present study revealed that microsatellites can be successfully utilized for assessment of genetic diversity to establish relationships among the germplasm lines of cowpea.